Harmonic Distortion Assessment of Nonlinear Medical Loads in a Hospital Distribution Network Using ETAP Simulation - Mangopo, Dultudes; Rimbawati; Harahap, Partaonan; Nurdiansyah (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2026)
The growing use of power-electronics-based medical equipment has significantly altered the load characteristics of hospital electrical distribution systems. As nonlinear devices increase, harmonic distortion becomes a critical power quality concern that may affect equipment reliability and operational safety. This study investigates harmonic behavior in a 20 kV/0.4 kV hospital distribution network through harmonic load flow simulation using ETAP software. Total Harmonic Distortion of Voltage (THDv) and Total Harmonic Distortion of Current (THDi) are evaluated at selected buses and at the Point of Common Coupling (PCC), with reference to IEEE Std. 519-2014. Simulation results indicate that two low-voltage buses supplying high-capacity medical equipment exhibit THDv values of 8.21% and 6.74%, exceeding the recommended 5% limit. The THDi at the PCC reaches 14.37%, surpassing the allowable limit for the calculated short-circuit ratio (Isc/IL = 8.43). Dominant harmonic components are identified at the 5th and 7th orders, confirming the influence of rectifier-based medical systems and UPS units. The findings demonstrate that nonlinear medical loads significantly contribute to harmonic propagation, increased branch losses, and voltage distortion. Appropriate mitigation strategies, including harmonic filtering and load configuration adjustments, are therefore essential to ensure compliance with power quality standards and to maintain reliable hospital operation.